Molecular and pathotypic characterization of fowl adenovirus associated with inclusion body hepatitis in Indian chickens - DASHARATH B SHINDE; ANIL L THORMOTHE; SANTOSH S KORATKAR; NEETI SHARMA; ASHOK RAJGURU; VINAY RALE; PRASAD WAGH; TEGUH Y PRAJITNO; SATISH S TONGAONKAR (Indian Journal of Animal Sciences, 2020)
Inclusion body hepatitis (IBH) is a disease of chickens characterized by acute mortality with severe anemia caused by fowl adenoviruses (FAdV). IBH is one of the most important re-emerging diseases worldwide. In India earlier IBH/ Hydropericardium Syndrome (HPS) outbreaks were mainly due to (FAdV) type 4; however, in recent outbreaks, other serotypes are involved, despite regular vaccination in breeders and young chicks. The aim of the present study was isolation and molecular characterization of FAdV associated with IBH in India. A total of 193 liver samples of IBH suspected broiler chickens were collected from different regions of India. Liver samples were initially screened by histopathology and further, a total of 127 samples which microscopically showed basophilic, intra-nuclear inclusion bodies were processed for FAdV detection. A total of 69 samples were found to be positive for Hexon gene in PCR, of which 28 were sequenced. These samples showed more than 94% sequence homology with FAdV2 and 97% with FAdV11, which was confirmed by Restriction Enzyme Analysis (REA). Tissue Culture Infective Dose50 (TCID50) and Egg Infective Dose50 (EID50) titer of isolated FAdV was found to be 106.5/ml. Pathogenicity study in SPF chicks showed 100% mortality up to Post Infection Day (PID)-6. These findings conclude that the prevalence of FAdV-11 is currently causing IBH outbreaks India. However, further genetic and pathogenic analysis of FAdV is required, which would provide useful information for the development of the efficient commercial IBH vaccine.